AN ANALYSIS OF ENGLISH AND UZBEK PROVERBS INVOLVING ANIMAL IMAGES DEPICTING HUMAN IDENTITIES (Archive of Conferences, 2021)
The following article gives a piece of information related to proverbs involving animal images depicting human identities in both languages which are English and Uzbek, as well as, differences between languages for proverbs are discussed.